WEWENANG DAN TANGGUNG JAWAB HUKUM KURATOR ATAS KESALAHAN ATAU KELALAIANNYA MENGAKIBATKAN KERUGIAN BAGI DEBITOR DALAM PROSES HUKUM PENGURUSAN DAN PEMBERESAN HARTA PAILIT - Aprita, Serlika (Faculty of Law, University of Palembang, 2019)
ABSTRACT In general, the monetary crisis that hit a country gave an unfavorable influence on the economic life of the country concerned and caused great difficulties in the business community to continue its activities. The ability of the business world to develop its business is very disturbed, even to maintain the continuity of its business activities is also not easy. It was decided that a debtor becomes a bankrupt debtor by the Commercial Court, it will cause legal consequences for the debtor and his assets. In connection with the loss of the right to control and manage the assets of the debtor, the curator has the authority to administer and deposit bankrupt assets. However, in its implementation, the curator has done a lot of mistakes and negligence in carrying out his duties, as found in various case examples, so the debtor must be responsible for errors and omissions. The existence of legal ratios as well as the form and mechanism of curatory legal responsibility has been regulated in Law Number 37 of 2004 based on the theory of legal responsibility and legal protection theory and the opinions of bankruptcy law experts are the main basis for curators to be responsible for their errors or omissions. It is expected that the curator in carrying out his duties to manage and deposit bankrupt debtors' assets can maximally increase the value of bankrupt assets in the interest of creditors.